Laboratory Changes During Dupilumab Treatment for Atopic Dermatitis - D. Flor; C. Montero-Vilchez; T. Montero-Vilchez; S. Arias-Santiago; M. Gonçalo (Actas Dermo-Sifiliográficas)
Introduction: Dupilumab is an IL-4/IL-13 inhibitor monoclonal antibody approved for the treatment of moderate-to-severe atopic dermatitis (AD) with remarkable safety and efficacy profiles. However, former studies have reported an increase in serum eosinophils during treatment, with undetermined clinical significance.The objective of this study is to evaluate changes in blood eosinophils and other laboratory parameters while on dupilumab. Methods: We conducted a multicenter, prospective, observational study from 2018 to 2022 with adolescent and adult patients with moderate-to-severe atopic dermatitis treated with dupilumab from Hospital Universitario Virgen de las Nieves, Spain, and Coimbra University Hospital, Portugal. Clinical scoring of the dermatitis, complete blood count, total serum IgE and LDH levels were collected at baseline and on weeks 8, 16, 24 and 48. Results: We included a total of 81 patients (41 women/40 men; mean age of 30.86 ± 12.26 years). Clinical and demographic characteristics were similar across centres. AD severity scales (EASI, SCORAD, ItchVAS and SleepVAS) showed sustained improvement from week 8 of treatment onwards. Eosinophil levels were significantly higher on week 16 (0.69 × 103/μL) vs baseline (0.41 × 103/μL) (p = 0.018) and returned to baseline levels on week 48 (0.59 × 103/μL, p > 0.05). LDH and IgE levels decreased during the study. Conclusion: Our study showed a significant clinical improvement of AD but a mild and self-limited increase in eosinophil levels on week 16, not associated with any clinical signs. Therefore, elevated serum eosinophil levels in AD patients on dupilumab does not seem clinically relevant and should not condition treatment withdrawal. Resumen: Introducción: Dupilumab es un anticuerpo monoclonal inhibidor de la IL-4/IL-13 aprobado para el tratamiento de la dermatitis atópica (DA) con perfiles de eficacia y seguridad notables. Sin embargo, estudios previos han informado de un aumento de los eosinófilos séricos durante el tratamiento, con un significado clínico indeterminado.El objetivo de este estudio es evaluar los cambios en los eosinófilos en sangre y otros parámetros de laboratorio durante el tratamiento con dupilumab. Métodos: Se realizó un estudio observacional prospectivo multicéntrico entre 2018 y 2022 con pacientes adolescentes y adultos con DA moderada a grave tratados con dupilumab del Hospital Universitario Virgen de las Nieves, España, y del Hospital Universitario de Coimbra, Portugal. Se recogieron puntuaciones clínicas de la dermatitis, hemograma completo, IgE sérica total y niveles de LDH al inicio y en las semanas 8, 16, 24 y 48 de tratamiento. Resultados: Se incluyeron 81 pacientes (41 mujeres/40 hombres; edad media de 30,86 ± 12,26 años). Las características clínicas y demográficas fueron similares entre centros. Las escalas de gravedad de la DA (EASI, SCORAD, ItchVAS y SleepVAS) mostraron una mejoría sostenida a partir de las 8 semanas de tratamiento. Los niveles de eosinófilos fueron significativamente mayores en la semana 16 (0,69 x103/μL) que al inicio (0,41 x103/μL) (p = 0,018) y volvieron a los niveles basales en la semana 48 (0,59 x103/μL, p >0,05). Los niveles de LDH e IgE disminuyeron durante el estudio. Conclusión: Nuestro estudio mostró una mejoría clínica significativa de la DA de los pacientes tratados con dupiluman, con un aumento leve y autolimitado de los niveles de eosinófilos en la semana 16, no asociado a ninguna manifestación clínica. Por lo tanto, el aumento de los eosinófilos séricos en pacientes con DA tratados con dupilumab no es clínicamente relevante y no debe condicionar la suspensión del tratamiento.